PENGARUH MOTIVASI, KOMUNIKASI DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN SHOPEE XPRESS DI WONOGIRI - Idam Ayub Fathoni; MG. Sukamdiani; Dwinda Agustintia (JURNAL ILMIAH EDUNOMIKA, 2025)
The problem formulation in this study is: Do Work Motivation, Communication, and Work Stress affect Employee Job Satisfaction at Shopee XPress in Wonogiri, both partially and simultaneously? Which variable has the most dominant effect on Job Satisfaction of Shopee XPress Employees in Wonogiri? Based on calculations using the SPSS program, the multiple linear regression equation obtained is Y = -0.532 + 0.557X1 + 0.263X2 + 0.268X3. In the t-test analysis for the Motivation variable, the calculated t-value is 4.796 > t-table 2.093, so Ho is rejected, meaning there is an effect of the Motivation variable on the Job Satisfaction of Shopee XPress Employees in Wonogiri (Y). In the t-test analysis, the t-value for Communication (X2) is 2.177 > t-table 2.093, so Ho is rejected. This means there is an effect of the Communication variable on Job Satisfaction of Shopee XPress Employees in Wonogiri (Y). In the t-test analysis, the t-value for Work Stress (X3) is 2.150 > t-table 2.093, so Ho is rejected. This indicates an effect of the Work Stress variable on the Job Satisfaction of Shopee XPress Employees in Wonogiri (Y). Based on the F-test analysis, the calculated F-value is 117.730 > F-table 3.13, so Ho is rejected, meaning that jointly, the independent variables of Motivation (X1), Communication (X2), and Work Stress (X3) affect the Job Satisfaction of Shopee XPress Employees in Wonogiri (Y). Using the SPSS program, the R2 value obtained is 0.762 or 76.2%, meaning that together, the independent variables of Motivation (X1), Communication (X2), and Work Stress (X3) have an influence of 76.2% on the Job Satisfaction of Shopee XPress Employees in Wonogiri (Y), while the remaining 23.8% is influenced by other factors not studied, such as infrastructure, technology, services, location, etc. Keywords: Motivation, Communication, Work Stress, Job Satisfaction